Abram as Israel, Israel as Abram: Literary Analogy as Macro-Structural Strategy in the Torah - Seth D. Postell (Tyndale Bulletin, 2016)
The argument is made that through the use of literary devices, the individual stories of the Abram narrative (Genesis 11–15) were strategically arranged to correspond with Israel’s story as told in the Book of Exodus. Although previous commentators have observed some parallels between these two stories, this article asserts that the reach of this literary analogy extends further than a few identifiable similarities, and reveals an overarching compositional strategy. Potential meanings of this analogy vis-à-vis its similarities and differences are explored, and the use of this extended literary analogy is considered as a framework for appreciating the NT’s figural interpretation of some Pentateuchal narratives.